Cyanide detection in gastric juice with corrin-based chemosensors. Issue 22 (23rd October 2015) - Aebersold, Christine; Amstutz, Beat; Steuer, Andrea E.; Kraemer, Thomas; Zelder, Felix
Abstract : This technical note describes the detection of cyanide in artificial gastric juice with corrin-based chemosensors. The application of this method in authentic human samples is demonstrated in a proof-of-principle forensic investigation. Abstract : This technical note describes the detection of cyanide in artificial gastric juice with corrin-based chemosensors. The application of this method in authentic human samples is demonstrated in a proof-of-principle forensic investigation.